Research progress in the treatment of cardiovascular diseases with extracellular vesicles - Jiang, Zhaoyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Extracellular vehicles (EVs) are small lipid vesicles that can release signaling substances containing proteins, nucleic acids, and other bioactive molecules. Recent research shows that EVs have potential application prospects in the treatment of cardiovascular diseases. EVs can alter the function of damaged cells and promote the repair and regeneration of cardiovascular tissue by transmitting bioactive molecules. In addition, EVs have the characteristics of low immunogenicity and high stability, making it a potential therapeutic strategy for cardiovascular diseases. Although the current research is still in the pre-clinical stage, with the further revelation of the mechanism of cardiovascular disease treatment using EVs, the treatment of cardiovascular diseases by EVs is bound to enter the clinical stage. This review expounds the advantages of EVs in cardiovascular diseases, and systematically lists the current application progress of EVs in a variety of cardiovascular diseases.